The attitude of undergraduates towards E-learning considering educational and technical challenges and requirements in Kuwaiti Applied Colleges - Hamed Alsahou; Zainab Abbas; Ali Alfayly (OmniaScience, 2022)
Digital learning has become one of the constituent elements of higher education in many countries. E-learning platforms provides remarkable opportunities to creatively overcome many problems of traditional learning approaches. Nevertheless, E-learning is not flawless, where there are many educational and technical difficulties of implementing online learning in higher education, especially when higher education stands on applied learning. The current study aims to explore undergraduates' attitudes towards E-learning in applied colleges. It also seeks to expose the most central educational and technical challenges of e-learning. Moreover, it drives to define the educational and technical requirements for ensuring quality e-learning. the research sample consisted of 1650 undergraduates and 37 interviewees who are drawn from five applied colleges in Kuwait (the College of Basic Education, the College of Technological Studies, the College of Business Studies, the College of Health Science, and the College of Nursing). The research design is based on mixed methods (questionnaire and focus groups).  The findings revealed that students held neutral attitudes towards e-learning, while the educational and technical challenges are high concerns. Educational challenges and requirements highlighted several themes including instructional support, progress valuation, self-study skills, attention span, interactivity, and class size. Meanwhile, the technical challenges include poor internet connectivity, IT support, LMS interface, training courses. Then, the findings are discussed to draw recommendations and implications.